Freezing theoretical approaches and empirical domains - Hartmann, Jutta (OAPEN (Open Access Publishing in European Networks)., 2018)
Displacement is a fundamental property of human language, and the restrictions on displacement have been a central concern in generative grammar ever since Ross' (1967) ground-breaking observations of island constraints. While island phenomena have been investigated in detail from various perspectives, a different domain, the domain of Freezing, originally defined in terms of non-base structures, has received far less attention. This volume brings together papers that address the questions of: What are the different concepts of Freezing? Which empirical domains can they explain? Is Freezing a core-syntactic restriction or does information structure, or processing play a role? The collection of papers provides insights into the empirical basis of the Freezing Principle in relation to other restrictions on extraction in order to contribute to a broader understanding of the nature of restrictions on displacement in language. The overall goal of the volume is a reconsideration of Freezing and other (sub-)extraction phenomena, both from a theoretical and empirical perspective, by bringing together contributions from experts in the field to discuss and broaden our knowledge of the empirical range of Freezing phenomena as well as their explanation.